2018
DOI: 10.1111/clr.13385
|View full text |Cite
|
Sign up to set email alerts
|

Sinus floor elevation in sites with a perforated schneiderian membrane: What is the effect of placing a collagen membrane in a rabbit model?

Abstract: Objective To investigate the healing following sinus grafting in sites with a perforated schneiderian membrane repaired using a collagen membrane, compared to control sites without membrane perforation. Materials & Methods Following elevation of the sinus membrane in 16 rabbits, each sinus was assigned to one of the following groups: (a) intentional schneiderian membrane perforation, followed by the placement of a collagen membrane and bone grafting (group SMP) and (b) bone grafting without a perforation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…The results from the present study are not in agreement with those from another experimental study in rabbits [18]. In that experiment, a perforation was intentionally produced in the sinus mucosa of the test sites and a collagen membrane was placed as protection subjacent to the sinus mucosa.…”
Section: Discussioncontrasting
confidence: 99%
“…The results from the present study are not in agreement with those from another experimental study in rabbits [18]. In that experiment, a perforation was intentionally produced in the sinus mucosa of the test sites and a collagen membrane was placed as protection subjacent to the sinus mucosa.…”
Section: Discussioncontrasting
confidence: 99%
“…Applying a resorbable collagen membrane to a perforated SM has been demonstrated to achieve a physical sealing effect, but its effects on healing of the SM and new bone formation are still unclear. A previous study found delayed new bone formation when using a collagen membrane and particulate bone on a perforated SM in a rabbit sinus model (Lim et al, 2018). It is assumed that the collagen membrane may impair the natural healing process of the SM by delaying the migration of undifferentiated basal cells from the adjacent untraumatized area or obstructing the osteogenic potential of the SM.…”
Section: Discussionmentioning
confidence: 90%
“…The use of PRF and CM for bone regeneration was analyzed in animal studies (Gavazzoni, Filho, & Hernandes, ; Horimizu et al, ; Lim et al, ; Oliveira et al, ; Padilha et al, ; Sun et al, ). In none of these cases, the combination of PRF and RCM was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In none of these cases, the combination of PRF and RCM was evaluated. However, the PRF was analyzed combined with Bio‐Oss (Oliveira et al, ), human‐cultured alveolar bone‐derived periosteal sheet (Horimizu et al, ), and leucocytes (Padilha et al, ); the RCM was associated with sinusal membrane (Lim et al, ), calcium sulfate and deproteinized bovine bone mineral (Gavazzoni et al, ), and cap morphogenetic protrein‐2 (Sun et al, ). In these studies, in general, the use of PRF showed better results with increased bone area increased after 60 days (Oliveira et al, ); increased angiogenesis at the site of application (Horimizu et al, ), positive effect on the regenerative process of bone defects, reduction of inflammatory response, and greater bone neoformation (Padilha et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation